THE POETICS OF CYBORG CHARACTERS IN BRUCE STERLING’S NOVELS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article theorizes the poetics of cyborg characterization in Bruce Sterling’s Schismatrix (and the Shaper/Mechanist stories), Islands in the Net, and selected pieces from Mirrorshades, using four complementary lenses—monologue, dialogue, landscape, and portrait—to map how posthuman identity is narrated, staged, situated, and embodied. I argue that Sterling’s cyborgs are defined less by disembodied transcendence than by hyper-embodied variability: interior focalization renders fluctuating selves under continuous technological revision; dialogic set-pieces externalize ideological conflict (Shaper biopolitics vs. Mechanist prosthetics) as ethical debate; world-building landscapes—from decaying orbital habitats and abyssal biomes to data-haven geopolitics—operate as evolutionary laboratories that select for divergent human futures; and portraiture, ranging from clinical catalogues of modification to baroque images of distributed, environmental bodies, turns the cyborg form into a readable archive of culture, power, and desire. Comparative readings with William Gibson (surface minimalism and iconic fetish objects), Marge Piercy (communitarian ethics and legal personhood), and Frederik Pohl (adaptive estrangement in alien ecologies) show Sterling’s distinct synthesis: doctrinal dialogues and materially luxuriant settings that bind technological change to socio-ecological histories. The article contributes a portable analytic—monologue/dialogue/landscape/portrait—for close-reading posthuman fiction and demonstrates how Sterling’s cyborgs transform from spectacular novelties into processual subjects, whose identities are iteratively authored by language, milieu, and flesh-tech assemblage. In Sterling’s work, the cyborg is not the end of the human but a poetics of becoming, where narrative form itself figures as an evolutionary mechanism.